2018
DOI: 10.1007/s00122-018-3120-8
|View full text |Cite
|
Sign up to set email alerts
|

When less can be better: How can we make genomic selection more cost-effective and accurate in barley?

Abstract: We were able to obtain good prediction accuracy in genomic selection with ~ 2000 GBS-derived SNPs. SNPs in genic regions did not improve prediction accuracy compared to SNPs in intergenic regions. Since genotyping can represent an important cost in genomic selection, it is important to minimize it without compromising the accuracy of predictions. The objectives of the present study were to explore how a decrease in the unit cost of genotyping impacted: (1) the number of single nucleotide polymorphism (SNP) mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 91 publications
7
40
0
Order By: Relevance
“…Linkage disequilibrium estimates in this population were extensive (average LD decay below .2 r 2 : 143 Mb). Several GP studies in barley have reported stable PA as marker density decreases (Abed et al, 2018;Lorenz et al, 2012;Nielsen et al, 2016), which support similar results in other crops (Lorenzana& Bernardo, 2009;Heffner et al, 2011;Spindel et al, 2016). Our results similarly support previous findings that marker density can be substantially reduced without a decrease in PA in malting barley.…”
Section: Methodssupporting
confidence: 92%
See 3 more Smart Citations
“…Linkage disequilibrium estimates in this population were extensive (average LD decay below .2 r 2 : 143 Mb). Several GP studies in barley have reported stable PA as marker density decreases (Abed et al, 2018;Lorenz et al, 2012;Nielsen et al, 2016), which support similar results in other crops (Lorenzana& Bernardo, 2009;Heffner et al, 2011;Spindel et al, 2016). Our results similarly support previous findings that marker density can be substantially reduced without a decrease in PA in malting barley.…”
Section: Methodssupporting
confidence: 92%
“…Prediction accuracies from across-family prediction in CV A1 were high and resembled previously published results for heading date (.55) (Abed et al, 2018), plant height (.36-.86) (Lorenz & Smith, 2015;Lorenzana & Bernardo, 2009), and grain protein (.4-.82) (Lorenzana & Bernardo, 2009;Nielsen et al, 2016). Lorenzana and Bernardo (2009) reported PA in biparental families for height (.90) and grain protein (.83) that surpass results from CV A1 and CV W1 in this study, but their datasets include 9-16 environments.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…In addition, recent studies have documented that relatively low-density genotyping can be as efficient as high-density genotyping in many cases (Raoul et al, 2016). For example, Abed et al (2018) showed that no significant decrease in the accuracy of genomic selection was seen when using as few as~1K SNPs compared to using 35K SNPs, even in a species such as barley that has a large genome (5.3 Gb). Gorjanc et al (2015) explored and evaluated the impact of increased multiplexing level by decreasing sequencing coverage (from 20 to 0.05x) in livestock genomic selection populations of 500k to 50k individuals.…”
Section: Scalability For Large-scale Multiplexingmentioning
confidence: 99%